Effect of Pericytes on Cerebral Microvasculature at Different Time Points of Stroke. (22nd December 2021) - Di, Zhong; Wu, Xin; Xie, Wei; Lin, Xianming
Abstract : Pericyte, as an important component of the blood-brain barrier, has received increasing attention in the study of cerebrovascular diseases. However, the mechanism of pericytes after the occurrence of cerebral ischemia is controversial. On the one hand, the expression of pericytes increases after cerebral ischemia, constricting the blood vessels to restrict blood supply and aggravating the damage caused by ischemia; on the other hand, pericytes participate in capillary angiogenesis in the ischemic area, which facilitates the repair of the ischemic injury area. The multifunctionality of pericytes is an important reason for this phenomenon, but the different time points of observation for the outcome indicators in each study are also an important factor that leads to the controversy of pericytes. Based on the review of a large database of original studies, the authors' team summarized the effects of pericytes on cerebral microvasculature at different time points after stroke, searched the possible markers, and explored possible therapeutic.